Pyruvate Research and Clinical Application Outlooks A Revolutionary Medical Advance - Fang-Qiang Zhou (International Journal of Nutrition, 2020)
Pyruvate holds superior biomedical properties in increase of hypoxia tolerance, correction of severe acidosis, exertion of anti-oxidative stress and protection of mitochondria against apoptosis, so that it improves multi-organ function in various pathogenic insults. Particularly, pyruvate preserves key enzyme: pyruvate dehydrogenase (PDH) activity through direct inhibition of pyruvate dehydrogenase kinas (PDK), as a PDH activator, in hypoxia. Therefore, pyruvate is robustly beneficial for cell/organ function over citrate, acetate, lactate, bicarbonate and chloride as anions in current medical fluids. Pyruvate-enriched oral rehydration salt/solution (Pyr-ORS) and pyruvate-based intravenous (IV) fluids would be more beneficial than WHO-ORS and current IV fluids in both crystalloids and colloids, respectively. Pyruvate-containing fluids as the new generation would be not only a volume expander, but also a therapeutic agent simultaneously in fluid resuscitation in critical care patients. Pyruvate may be also beneficial in prevent and treatment of diabetes, aging and even cancer. Pyruvate clinical applications indicates a new revolutionary medical advance, following the WHO-ORS prevalence, this century.
Keywords: Aging